(untitled) (Journal of Electrochemical Science and Engineering, 2019)
Microbial fuel cells use bacteria to generate electrical energy and are used for lower power density applications. This paper studies the effect of operational parameters on the performance of a microbial fuel cell. The effect of length of the anode compartment, inlet acetate concentration, acetate flow rate, temperature, thickness of the membrane and bio-film conductivity on the performance of the fuel cell is modeled. The thickness of the membrane is found to play a very limiting role in affecting the performance of the fuel cell. However, the length of the anode compartment, acetate flow rate and bio-film conductivity are found to play a significant role in the performance of the fuel cell. Model results are compared with experimental data and found to compare well.